Antiproliferative activity of 8-methoxypsoralen on DU145 prostate cancer cells under UVA and blue light. Issue 7 (12th June 2017) - Sturaro, Giulio; Cigolini, Giulia; Menilli, Luca; Cola, Fabio; Di Liddo, Rosa; Tasso, Alessia; Conconi, Maria Teresa; Miolo, Giorgia
Abstract : The use of photoactivatable 8-methoxypsoralen (8-MOP) as potential focal treatment towards prostate cancer cells is proposed here. Abstract : The use of photoactivatable 8-methoxypsoralen (8-MOP) as potential focal treatment towards prostate cancer cells is proposed here. Our results, obtained on isolated DNA and DU145 cells, indicate that blue light, besides UVA, is able to activate 8-MOP. When compared to UVA, blue light irradiation led to a modulation of the extent and the types of 8-MOP-DNA damage, specially cross-links, coupled to a still valuable antiproliferative effect. Our data suggest that the proapototic activity of 8-MOP is related not only to DNA damage and reactive oxygen species generation but also to the modulation of cell signalling pathways. In particular, a different activation of p38 and p44/42 mitogen-activated protein kinases was detected depending on the light wavelengths.